Effect of Mineral Trioxide Aggregate, Calcium Enriched Mixture and Mineral Trioxide Aggregate with Disodium Hydrogen Phosphate on BMP-2 Production - Ghasemi, Negin; Rahimi, Saeed; Lotfi, Mehrdad; Solaimanirad, Jafar; Shahi, Shahriar; Shafaie, Hajar; Salem Milani, Amin; Shakuie, Sahar; Zand, Vahid; Abdolrahimi, Majid (Iranian Endodontic Journal, 2014)
Introduction: One of the hypotheses regarding the calcification induction by mineral trioxide aggregate (MTA) is the involvement of transforming growth factor-Beta (TGF-β) super family. Calcium-enriched mixture (CEM) cement is one of the endodontic biomaterials with clinical applications similar to MTA. The aim of the present in vitro study was to compare the induction of bone morphogenic protein-2 (BMP-2) by a combination of disodium hydrogen phosphate (DSHP) and tooth colored ProRoot MTA (WMTA), to that of CEM cement and WMTA. Methods and Materials: Human gingival fibroblasts (HGFs) were obtained from the attached gingiva of human premolars. HGFs were cultured in Dulbecco’s Modified Eagle’s medium, supplemented with 10% fetal calf serum, penicillin, and streptomycin. Cells in groups 1, 2 and 3 were exposed to WMTA, CEM and WMTA+DSHP discs, respectively. The fourth group served as the control. After 72 h of exposure, HGF viability was determined by Mosmann’s tetrazolium toxicity (MTT) assay. BMP-2 levels in cell-free culture media were determined by enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using the one-way ANOVA, followed by the post hoc Games-Howell test for BMP-2 and post hoc Tukey’s test for the results of MTT assay. Results: Cellular viability was significantly higher in group 3 compared to the other groups (P<0.05); however, CEM and WMTA did not exhibit significant differences (P=0.08). The control group exhibited significantly higher cellular viability in comparison to the other groups of the study (P<0.05). The highest and lowest protein production rates were observed in the WMTA (3167±274.46 pg/mL) and WMTA+DSHP (1796±839.49 pg/mL) groups, respectively. There were no significant differences between the control, WMTA and CEM groups (P>0.05). Conclusion: WMTA and CEM did not exhibit any significant differences in inducing BMP-2 production compared to control; however, incorporation of DSHP into WMTA resulted in a decrease in the induction of this protein.